2016
DOI: 10.1007/s11325-016-1408-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting CPAP adherence in obstructive sleep apnea syndrome

Abstract: The present findings should be further explored in order to tailor interventions to the specific needs of different patient profiles and secure an improved CPAP adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 30 publications
1
30
2
4
Order By: Relevance
“…Median adherence time was 957 days. It also highlighted an adherence of 70.3% at 6 months and 49.3% at 8 years [3].…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Median adherence time was 957 days. It also highlighted an adherence of 70.3% at 6 months and 49.3% at 8 years [3].…”
mentioning
confidence: 85%
“…Each contact with the service provider reduced the risk of non-adherence to CPAP by 18% (HR = 0.847), marking the importance of a patient support program that could promote education on the optimal use of the CPAP. Spouse encouragement plays also an important role [3]. This was highlighted in a meta-analysis by Wozniak et al [8] that showed that support interventions were linked to slightly better adherence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…
To the editor, We have a great interest in the recently published article entitled BFactors predicting CPAP adherence in obstructive sleep apnea syndrome^by M. Riachy et al [1]. The authors studied the determinants of short-term and long-term CPAP adherence in a group of Lebanese patients.
…”
mentioning
confidence: 99%